Complete mitochondrial genome of a Neotropical dobsonfly Chloronia mirifica Navás, 1925 (Megaloptera: Corydalidae), with phylogenetic implications for the genus Chloronia Banks, 1908 - Jiang, Yunlan; Yang, Fan; Yang, Ding; Liu, Xingyue (Zootaxa, 2016)
The complete mitochondrial (mt) genome of Chloronia mirifica Navás, 1925 was determined and analyzed. This represents the first mt genome of the Neotropical endemic dobsonfly genus Chloronia Banks, 1908. The mt genome of C. mirifica is a typical circular DNA of 15877 base pairs with an A+T 77.1%. It has an ancestral gene arrangement of the insect mt genome composed of 37 genes. Eleven of the 13 protein coding genes (PCGs) start with ATT and ATG, while nad6 and nad1 start with ATC and TTG respectively. Five PCGs end with a single T, while the others have a complete termination codon TAG or TAA. Most tRNAs are folded into the typical clover-leaf structure except for the trnS1 whose dihydrouridine arm is a simple loop. The secondary structure of rrnL consists of five structural domains and 50 helices, while the rrnS includes three domains and 34 helices. The phylogenetic analysis based on all 13 PCGs and two rRNA genes of the mt genome recovers Chloronia to be the sister group of Corydalus Latreille, 1802.